Extracellular chromosome 21-derived microRNAs in euploid & aneuploid pregnancies - Kotlabova, Katerina; Doucha, Jindrich; Chudoba, Daniel; Calda, Pavel; Dlouha, Klara; Hromadnikova, Ilona (The Indian journal of medical research, 2013)
BACKGROUND & OBJECTIVES: Trisomy 21 is the most common chromosomal aneuploidy in live born infants. Recently, the over expression of chromosome 21-derived microRNAs (miR-99a, let-7c, miR-125b-2, miR-155 and miR-802) in human fetal hippocampus and heart samples from individuals with Down syndrome was observed. Therefore, concentrations and expression profile of extracellular chromosome 21-derived microRNAs were studied to verify their ability to distinguish noninvasively between pregnancies bearing euploid fetuses and those affected with Down syndrome. METHODS: RNA enriched for small RNAs was isolated from plasma samples of 12 pregnant women with high risk of bearing Down syndrome foetuses (median gestation 18.5 wk), 12 women with normal course of gestation and 10 non-pregnant women. MicroRNA transcribed into cDNA using specific stem-loop primer was detected using real-time PCR assay. Simulation experiments using RNA pools of healthy non-pregnant individuals and aneuploid amniotic fluid samples in descending dilution ratio ranging from 1:1 to 1000:1 were used to test the detection limit of the technique for overexpressed chromosome 21-derived microRNAs specific for Down syndrome. The expression profile of the gene encoding microRNA was studied through the relative gene expression using the comparative Ct (threshold cycle) method. Concentrations of individual microRNAs were subtracted from the calibration curves in the course of analyses and expressed as pg of total RNA per milliliter of plasma. RESULTS: Four of the five extracellular chromosome 21-derived microRNAs (miR-99a, let-7c, miR-125b-2 and miR-155) were reliably detected in plasma samples. Simulation experiments revealed the detection limit of aneuploidy at a ratio 100:1 for let-7c, miR-125b-2 and miR-155, and a ratio of 1000:1 for miR-99a. Overexpression of extracellular miR-99a, miR-125b-2 and miR-155 was observed in pregnant women compared to non-pregnant women. Similarly, increased concentrations of extracellular miR-99a and miR-125b-2 were detected in pregnant women than in non-pregnant women. The concentrations and relative gene expression of extracellular chromosome 21-derived microRNAs did not differ between the cohorts of pregnancies bearing euploid foetuses and those affected with Down syndrome. INTERPRETATION & CONCLUSIONS: Analysis of extracellular chromosome 21-derived microRNAs has no benefit for screening programmes and non-invasive diagnosis of Down syndrome.
Keywords: diploidie; aneuploidie; Diploidy; těhotenství; vývojová regulace genové exprese; Chromosomes, Human, Pair 21; mikro RNA; plod; Adult; Downův syndrom; Aneuploidy; MicroRNAs; Gene Expression Regulation, Developmental; lidské chromozomy, pár 21; ženské pohlaví; Humans; Pregnancy; dospělí; Fetus; Female; Down Syndrome; lidé